2017
DOI: 10.1038/s41598-017-09519-0
|View full text |Cite
|
Sign up to set email alerts
|

Emotional over- and under-eating in early childhood are learned not inherited

Abstract: Emotional overeating (EOE) has been associated with increased obesity risk, while emotional undereating (EUE) may be protective. Interestingly, EOE and EUE tend to correlate positively, but it is unclear whether they reflect different aspects of the same underlying trait, or are distinct behaviours with different aetiologies. Data were from 2054 five-year-old children from the Gemini twin birth cohort, including parental ratings of child EOE and EUE using the Child Eating Behaviour Questionnaire. Genetic and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 55 publications
7
61
0
2
Order By: Relevance
“…Other research has examined and reported possible differences in processes between boys and girls . Finally, at times, sex/gender differences have not been found and/or data for boys and girls have been combined . There appears to be no consistent position in the literature in relation to possible sex/gender differences in processes and pathways to OW/OB in childhood.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Other research has examined and reported possible differences in processes between boys and girls . Finally, at times, sex/gender differences have not been found and/or data for boys and girls have been combined . There appears to be no consistent position in the literature in relation to possible sex/gender differences in processes and pathways to OW/OB in childhood.…”
Section: Resultsmentioning
confidence: 97%
“…The model in Figure recognizes the role of parental influences on the development of OW/OB in childhood. The contribution of these psychosocial processes is prominent in the developmental literature and scholarship on the development of children's eating and weight . A biopsychosocial approach emphasizes the need to integrate these psychosocial influences with child biological factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such adverse effects on health underscore the importance of understanding the etiology of these eating behaviors, but unfortunately, research on their precursors is lacking. Notably, the results of two recent twin studies showed that the shared family environment plays an important role in shaping both emotional over‐ and undereating (Herle, Fildes, Rijsdijk, Steinsbekk, & Llewellyn, ; Herle, Fildes, Steinsbekk, Rijsdijk, & Llewellyn, ). What the twin studies could not illuminate, however, were the specific nongenetic factors that might influence emotional over‐ and undereating.…”
Section: A Model Of Emotional Over‐ and Undereating In Childrenmentioning
confidence: 99%
“…However, the most natural response to emotional distress is to eat less due to biological mechanisms: Gut activity decreases in the presence of emotional arousal, which suppresses hunger (van Strien & Ouwens, ). Given that emotional over‐ and undereating have some common etiology (Herle, Fildes, Steinsbekk, et al., ) and tend to be positively associated with each other (Herle, Fildes, Steinsbekk, et al., ; Wardle et al., ), it is reasonable to assume that overlapping etiological forces are at play in both eating behaviors.…”
Section: A Model Of Emotional Over‐ and Undereating In Childrenmentioning
confidence: 99%